ChAMP: 450k Chip Analysis Methylation Pipeline - Morris, Tiffany J.; Butcher, Lee M.; Feber, Andrew; Teschendorff, Andrew E.; Chakravarthy, Ankur R.; Wojdacz, Tomasz K.; Beck, Stephan (Bioinformatics, 2014)
The Illumina Infinium HumanMethylation450 BeadChip is a new platform for high-throughput DNA methylation analysis. Several methods for normalization and processing of these data have been published recently. Here we present an integrated analysis pipeline offering a choice of the most popular normalization methods while also introducing new methods for calling differentially methylated regions and detecting copy number aberrations. Availability and implementation: ChAMP is implemented as a Bioconductor package in R. The package and the vignette can be downloaded at bioconductor.org Contact:  tiffany.morris@ucl.ac.uk